KEMUKJIZATAN AL-QUR’AN: TELAAH KEMUKJIZATAN AL-QUR’AN MELALUI KEAKURATAN BILANGAN - Maulana Maulana (Borneo : Journal of Islamic Studies, 2020)
Al-Qur’an is the kalamullah that was sent down to the prophet Muhammad SAW. through the angel Gabriel, in which contains the guidelines for life for all humans. The life guidelines described in the Koran are still very global and general, because of this generality, the scholars try to understand and interpret them using various methods and their respective ways. al-Qur'an and science are a challenge for the al-Qur'an. If the Qur'an has absolute and absolute dimensions, on the contrary, modern knowledge is dynamic and changes along with scientific discoveries. Then what if the Qur'an is understood from the perspective of modern science? This explains that one way of understanding the Qur'an is through modern science. In other words, there is no contradiction between the Qur'an and science. In fact, if Muslims want to understand the Qur'an in depth, of course they will find the truth and scientific proof in it.